Metaplastic breast cancers: Genomic profiling, mutational burden and tumor-infiltrating lymphocytes. (April 2019) - Tray, Nancy; Taff, Jessica; Singh, Baljit; Suh, James; Ngo, Nhu; Kwa, Maryann; Troxel, Andrea B.; Chae, Young Kwang; Kurzrock, Razelle; Patel, Sandip Pravin; Sharon, Elad; Denkert, Carsten; et al.
Abstract: Metaplastic breast cancer (MPBC) is a rare subtype that accounts for <1% of all breast cancers. Although these are typically "triple negative, " they are relatively chemotherapy-refractory compared to conventional triple negative invasive breast cancers with more aggressive features and an overall poor prognosis. MPBC is a heterogeneous group of tumors that are enriched for TP53 and PIK3CA mutations, and have been found to have high PD-L1 expression though the mechanisms underlying its immunogenicity remain unclear. We perform comprehensive genomic profiling in the largest MPBC dataset (n = 192) to date and assess for other potential biomarkers of immune response. Highlights: MPBC are highly enriched for TP53 and PIK3CA mutations. High frequency of PD-L1 expression reported in MPBC is unrelated to gene amplification. MPBC in general have low TMB, but significant lymphocytic infiltration. MPBC are typically microsatellite stable. More studies are needed to assess mechanisms of immunogenicity for this rare subtype.